Recent advances in engineering nonribosomal peptide assembly lines. Issue 2 (24th December 2015) - Winn, M.; Fyans, J. K.; Zhuo, Y.; Micklefield, J.
Abstract : This reviews summarises progress towards the engineering of nonribosomal peptide synthetases (NRPS) from the expression of heterologous tailoring enzymes to direct modifications of the assembly lines to produce analogues. New techniques/tools for introducing changes are also examined. Abstract : Covering: up to July 2015 Nonribosomal peptides are amongst the most widespread and structurally diverse secondary metabolites in nature with many possessing bioactivity that can be exploited for therapeutic applications. Due to the major challenges associated with total- and semi-synthesis, bioengineering approaches have been developed to increase yields and generate modified peptides with improved physicochemical properties or altered bioactivity. Here we review the major advances that have been made over the last decade in engineering the biosynthesis of nonribosomal peptides. Structural diversity has been introduced by the modification of enzymes required for the supply of precursors or by heterologous expression of tailoring enzymes. The modularity of nonribosomal peptide synthetase (NRPS) assembly lines further supports module or domain swapping methodologies to achieve changes in the amino acid sequence of nonribosomal peptides. We also review the new synthetic biology technologies promising to speed up the process, enabling the creation and optimisation of many more assembly lines for heterologous expression, offering new opportunities for engineering the biosynthesis of novel nonribosomal peptides.